GAMBARAN PERILAKU CARING PERAWAT DI RUANG FLAMBOYAN RSUP PROF. DR. I.G.N.G. NGOERAH - I Made Rai Darmika; M. Adreng Pamungkas; Ni Ketut Mirayanti (Sekolah Tinggi Pariwisata Mataram, 2023)
Caring is a basic soft skill of a nurse to make a good quality of service towards the patient in a hospital. As one of the ward in RSUP Prof. Dr. I.G.N.G Ngoerah, the study of nurse’s caring behavior in Flamboyan ward never done before. The aims of this research are to asses the characteristic of the sample (age, educational level, sex) and measure the caring behavior of the nurses. This research is a descriptive-non experimental research, using quantitative approach. The characteristics of the sample divided into age, sex and educational level. The caring behavoiur of the nurses were measured by using Swanson Caring Level instrument. This study shown the most of the respondents are male respondent (59,44%),, by the age, most of them are in the category of 36-45 years old (31,11%) and bythe educational level, most of them were undergraduate (42,78%). The result of the study shown that the level of caring behavior in a “Good” category are 76,67%. This study can be used as an evaluation of caring level of the nurse to maintain the quality of care to the patient.